Fish assemblage structure in a Neotropical urbanised prairie stream exposed to multiple natural and anthropic factors - Bertora, Andrea (2021)
A myriad of factors affect stream fish assemblages, and most of them are intimately regulated by surrounding land uses. One of the most pernicious impacts on streams is the release of urban effluents. Accordingly, understanding the fish assemblage patterns as well as the environmental drivers that modulate them in the context of urban streams which also are exposed to other land uses is mandatory. We evaluated the longitudinal patterns of fish assemblages in an urbanised Neotropical prairie stream exposed to downstream patches of different surrounding land uses. Several variables of water quality, in-stream habitat and riparian corridors were measured, and their relationships with fish metrics were explored. A fish metric selection protocol was implemented, and several multivariate analyses were used. Three main patterns of fish response were observed. Assemblage-level attributes as diversity, richness, biomass, number of families and trophic guilds and proportion of Characiformes and intolerant species were responsive to the natural gradient in habitat (pools) and riparian (riparian width) conditions expected in non-impacted lotic ecosystems. Conversely, a downstream continuum of recovery in water quality (dissolved oxygen, conductivity, NO3:NH4 and bacteriological loads) and habitat structure (sediment depth) would influence the distribution of fish species regarding their environmental tolerance and habitat preferences. Finally, local habitat aspects (nitrites, submerged macrophytes, bare soil cover and bank incisions by livestock) seemed relevant for the trophic structure (omnivorous species) of fish assemblages. A complex natural and anthropic longitudinal scenario together with local disruptions imposed by surrounding land uses were directive for fish.